SHIP CLASSIFICATION FROM MULTISPECTRAL VIDEOS - Robert-Inacio, Frederique; Oudinet, Ghislain; Colonna, Francois-Marie (Image Analysis and Stereology, 2012)
Surveillance of a seaport can be achieved by different means: radar, sonar, cameras, radio communications and so on. Such a surveillance aims, on the one hand, to manage cargo and tanker traffic, and, on the other hand, to prevent terrorist attacks in sensitive areas. In this paper an application to video-surveillance of a seaport entrance is presented, and more particularly, the different steps enabling to classify mobile shapes. This classification is based on a parameter measuring the similarity degree between the shape under study and a set of reference shapes. The classification result describes the considered mobile in terms of shape and speed.